Complete genome sequence of thermophilic Bacillus smithii type strain DSM 4216T. Issue 1 (December 2016) - Bosma, Elleke; Koehorst, Jasper; van Hijum, Sacha; Renckens, Bernadet; Vriesendorp, Bastienne; van de Weijer, Antonius; Schaap, Peter; de Vos, Willem; van der Oost, John; van Kranenburg, Richard
Abstract Bacillus smithii is a facultatively anaerobic, thermophilic bacterium able to use a variety of sugars that can be derived from lignocellulosic feedstocks. Being genetically accessible, it is a potential new host for biotechnological production of green chemicals from renewable resources. We determined the complete genomic sequence of theB. smithii type strain DSM 4216T, which consists of a 3, 368, 778 bp chromosome (GenBank accession number CP012024.1) and a 12, 514 bp plasmid (GenBank accession number CP012025.1), together encoding 3880 genes. Genome annotation via RAST was complemented by a protein domain analysis. Some unique features ofB. smithii central metabolism in comparison to related organisms included the lack of a standard acetate production pathway with no apparent pyruvate formate lyase, phosphotransacetylase, and acetate kinase genes, while acetate was the second fermentation product.